A Novel Cause of Bowel Obstruction in a Patient with Long-Standing Crohn’s Disease - Satya V. Vedula; T. Paul Nickerson; Douglas J. Grider (Case Reports in Pathology)
Solitary fibrous tumors are rare tumors of mesenchymal origin. Although most often observed in the lung pleura, they have been reported in varied extrapleural sites. A 70-year-old male with complicated Crohn’s disease presented with 3 days of nausea, emesis, constipation, and abdominal pain. Computed Tomography (CT) demonstrated mucosal thickening of the middescending colon, consistent with fibrosing stricture. Surgical excision revealed an unusual, 5 cm mass originating in the subserosa. Histopathology of the lesion was notable for a proliferation of cells with spindle and stellate-shaped nuclei and no appreciable mitotic figures, which extended into the muscularis and submucosa. Immunohistochemistry was STAT6 nuclear positive and cytoplasmic CD34 positive, diagnostic for solitary fibrous tumor (SFT). In this case, the SFT infiltrating into the muscularis propria and subserosa caused the stricture and bowel obstruction. This illustrates that while fibrosing strictures are usually the etiology of bowel obstruction in the setting of Crohn’s disease, other rare possible causes should be considered.